Outcome of Elderly Population Undergoing Primary PCI in a Tertiary Hospital in Bangladesh (Ibrahim Cardiac Medical Journal, 2021)
Objective: To evaluate in-hospital and 1-year outcomes of primary percutaneous coronary intervention (PPCI) in elderly patients with ST-elevation myocardial infarction (STEMI).Methods: All patients aged ≥ 65 years presenting with STEMI and undergoing PPCI at Ibrahim Cardiac Hospital & Research Institute, Bangladesh from January 2015 to August 2017 were consecutively included in the study based on predefined eligibility criteria. Data pertaining to angiographic characteristics, procedural variables, in-hospital and 1-year outcome variables were recorded and analyzed with the help of descriptive statistics and Chi-square Test.Results: The mean age of the patients was 69.2 ± 5.2 (range: 65-85) years with male to female ratio being 4:1. The patients were predominantly diabetic (78%) followed by hypertensive (74%) and dyslipidaemic (70%) smoker (54%). Half of the patients presented with anterior myocardial infarction (MI), 30% had inferior MI, 12% with right ventricular (RV) extension and 8% with inferolateral extension. About one-quarter (24%) had arrhythmia with complete heart block (CHB). The culprit arteries were LAD (50%), followed by RCA (42%) and LCx (8%). Nearly half (46%) had single vessel disease, 34% double and 20% triple vessel disease. Majority (80%) received a single stent and 20% required two stents with mean diameter and length of the stents were 2.9 ± 0.4 mm and 27.3 ± 7.9 mm respectively. Intracoronary eptifibatide was used in 20% cases. In terms of left ventricular ejection fraction (LVEF), 58% and 28% had mild and moderate LV systolic dysfunction respectively. The mean duration of hospital stay was 4.0 ± 1.9 days. About 18% required repeat hospitalization. Overall, 7(14%) patients died (4 during their stay in the hospital due to cardiac cause and 3 during follow up due to non-cardiac causes). At 1 year follow up, in-stent restenosis was seen in 1 case followed by target vessel revascularization (TVR). The Association between age and outcome revealed that advanced age (age ≥ 75 years) was an important predictor of in-hospital and one-year outcome with Relative Risk (RR) of having unfavorable outcome was > 5-fold (95% CI: 1.6-19.5) in patients of advanced age than that in patients of age < 75 years (p = 0.008).Conclusion: Primary PCI is a feasible treatment option for elderly Bangladeshi patients presenting with STEMI with fewer in-hospital and 1-year follow up deaths. Adverse cardiovascular events are even less. Advanced age (age ≥75 years) is an important determinant of adverse cardiovascular events including mortality, probably because of more medical co-morbidities associated with advanced age.Ibrahim Card Med J 2020; 10 (1&2): 18-26